More realistic estimates of revenue changes from tax cuts - Thor O. Thoresen; Jørgen Aasness; Zhiyang Jia (Statistics Norway, Research Department, 2008)
Procedures of revenue estimation of changes in the personal income tax are discussed. Using revenue estimates of the 2006 tax cuts in the personal income tax in Norway as an example, we show that estimates of costs of cuts differ substantially when different effects are brought into consideration. Estimates of revenue effects which take labor supply responses and effects through indirect taxation and corporate taxes into account are presented and contrasted with estimates obtained by current procedures. Our estimates indicate that a substantial part of the initial outlay is returned; approximately 56 percent comes back as increased tax revenues from other tax bases and increased personal income tax following from labor supply adjustments.
Keywords: H24; H31; 330; tax revenue estimates; scoring procedures; microsimulation